Complex Thinking, Planetary Ethics and Social Transformation in Teacher Education - López-Calva, Juan Martín (2022)
Introduction: The crisis that the world is experiencing today is demanding attention to the ethical training of the new generations. An essential element to attend it is the ethical training of teachers. Objective: To present the results of an exploratory research that investigated the opinion of teachers and experts in teacher training programs, on the ethical training of teachers from the loop: complex thinking-planetary ethics-social transformation. Method: A sample of 22 experts in teacher training and 222 teachers of different educational levels were surveyed, applying an exploratory questionnaire on the ethical training of teachers, constructed with a Likert scale of seven options. The results of the questions related to the loop described in the objective, which is part of the constructed theoretical proposal, are presented descriptively and comparatively. Results: show that there is not enough attention to the ethical training of teachers from  the dimensions: complex thought-planetary ethics-social transformation. Discussion: the opinion of the teachers is slightly more positive than that of the experts, although both groups show the insufficiency of teacher training in these areas. Being an exploratory study, it provides a first comparative look. It will be necessary to complement it with a qualitative study.